Perovskite solar cell capable of eliminating stress of perovskite thin film and preparation method of perovskite solar cell
By introducing small ions to the film of perovskite solar cells, the performance degradation caused by stress in perovskite films is solved, and efficient and stable photoelectric conversion efficiency and long-term stability are achieved.
Patent Information
- Application Number
- CN202411969094.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Stress problems in thin films in perovskite solar cells affect their stability and performance, resulting in reduced photoelectric conversion efficiency and shortened service life.
By introducing an appropriate amount of small ions (such as lithium ions and potassium ions) into the perovskite precursor, the stress distribution in the film is regulated, stress concentration phenomenon is reduced, and the crystallization quality and interface contact performance of the film are improved.
Effectively eliminate stress in the film, improve photoelectric conversion efficiency and long-term stability of the device, significantly improve the flatness and density of the film, and is suitable for commercial applications.
Smart Images

Figure CN119789739A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of optoelectronic materials and devices, and particularly relates to a perovskite solar cell capable of eliminating stress in a perovskite film by adding small ions and a preparation method thereof. Background Art
[0002] With the progress and development of society, energy crisis and environmental problems are becoming increasingly serious. The development of efficient, clean and renewable energy has become an important topic of global research. Solar energy is considered to be one of the best choices to replace traditional fossil energy because of its clean and sustainable characteristics. As a new generation of photovoltaic technology, perovskite solar cells have received extensive attention and research in recent years due to their advantages such as high photoelectric conversion efficiency, low cost and simple preparation. Since it was first reported in 2009, the photoelectric conversion efficiency of perovskite solar cells has rapidly increased from 3.8% to more than 25%. However, the practical application and commercialization of perovskite solar cells still face many challenges, among which the stress problem in perovskite films is one of the key factors affecting its stability and performance.
[0003] The stress in perovskite films mainly comes from the differences in the expansion coefficients of the materials or the inhomogeneity of the crystal growth process during the deposition and annealing of the films. The presence of stress can cause film cracking and increase grain boundary defects, which in turn affects the stability of the perovskite crystals, reduces the photoelectric conversion efficiency of the device, and shortens the service life of the device. Therefore, how to effectively eliminate the stress in perovskite films has become an important research direction for improving the performance and stability of perovskite solar cells. Summary of the invention
[0004] In order to solve the above defects existing in the prior art, the purpose of the present invention is to provide a method for eliminating stress in a perovskite film by introducing small ions. By introducing small ions during the preparation of the perovskite film, the stress distribution in the film is effectively regulated, and the prepared film surface is flat and dense, and the defect state density is low, thereby improving the crystallization quality of the film, reducing the defect state density, and improving the photoelectric conversion efficiency and long-term stability of the device. The prepared perovskite solar cell has excellent photoelectric conversion efficiency, and also exhibits excellent long-term stability and resistance to environmental erosion.
[0005] The present invention is achieved through the following technical solutions.
[0006] One aspect of the present invention provides a method for preparing a perovskite solar cell for eliminating perovskite film stress, comprising the following steps:
[0007] (1) Clean the FTO glass substrate, dry it, and then treat it with ultraviolet ozone;
[0008] (2) dissolving lead iodide, formamidine hydroiodide, methylamine hydrochloride and methylamine lead tribromide single crystal in a mixed solvent in a molar ratio of (1.5-1.6):(1.2-1.4):(0.3-0.5):(0.01-0.2) to obtain a perovskite precursor solution;
[0009] (3) dissolving tert-butylpyridine, tert-butylpyridine-sulfonyl imide solution, lithium bis(trifluoromethanesulfonyl imide) solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in an organic solvent in a mass ratio of (10-30):(1-10):(5-20):(10-100) to obtain a hole transport layer precursor solution;
[0010] (4) Preparation of SnO by chemical bath deposition on the cleaned FTO glass substrate 2 Electron transport layer;
[0011] (5) adding germanium iodide to a perovskite precursor solution on a FTO transparent conductive glass on which an electron transport material is deposited, and applying a spin coating method to the perovskite precursor solution; then applying a spin coating method using an anti-solvent method, and annealing to obtain a perovskite layer;
[0012] (6) spin coating a hole transport layer precursor solution on the FTO transparent conductive glass deposited with the perovskite layer to obtain a hole transport layer coated on the perovskite layer;
[0013] (7) A metal electrode is thermally evaporated on the FTO transparent conductive glass deposited with a hole transport layer to obtain a perovskite solar cell.
[0014] Preferably, the mixed solvent is prepared by mixing N,N-dimethylformamide / dimethyl sulfoxide in a mass ratio of (5-10):(1-10).
[0015] Preferably, the tert-butylpyridine-sulfonyl imide solution is prepared by dissolving 50-100 mg of tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris[bis(trifluoromethane)sulfonyl imide] in 100-1000 μL of acetonitrile in a mass ratio.
[0016] Preferably, the organic solvent is one or more of chlorobenzene, anisole or ethyl acetate.
[0017] Preferably, in step (5), the perovskite precursor solution is spin-coated by a spin coating method, comprising: treating the FTO transparent conductive glass on which the electron transport material is deposited with ultraviolet ozone, spinning the perovskite precursor solution in a nitrogen atmosphere at a low speed of 1000 to 2000 rpm for 10 to 20 seconds by a spin coating method, and then spinning at a high speed of 5000 to 7000 rpm for 20 to 40 seconds.
[0018] Preferably, in step (5), anti-solvent method spin coating and annealing are used, comprising:
[0019] Anhydrous ether is added as an antisolvent in the last 15 seconds, and the perovskite film is aged and annealed at 100-150°C for 0.5-3 hours; cooled to room temperature, spin-coated with iodate solution at a rotation speed of 3000-5000 rpm for 30-60 seconds, and immediately annealed at 100-150°C for 5-8 minutes.
[0020] Preferably, the iodate solution is n-octylamine hydroiodide or 4-methoxyphenethylammonium iodide dissolved in isopropanol at a concentration of 3.5-4 mg / mL.
[0021] Preferably, in step (6), the hole transport layer precursor solution is spin-coated on the FTO transparent conductive glass deposited with the perovskite layer at 4000-6000 rpm for 20-60 seconds;
[0022] In the step (7), the metal electrode thermally evaporated on the FTO transparent conductive glass deposited with the hole transport layer is a gold electrode with a thickness of 100 to 200 nm.
[0023] Another aspect of the present invention provides a perovskite solar cell prepared by the method and capable of eliminating the stress of the perovskite film.
[0024] The present invention adopts the above technical solution, which has the following beneficial effects:
[0025] 1. Effectively eliminate stress in the film: By introducing an appropriate amount of small ions (such as lithium ions, potassium ions, etc.) into the perovskite precursor solution, the small ions can enter the lattice or be located at the grain boundary during the formation of the perovskite film, significantly regulating the stress distribution in the film. This can effectively reduce stress concentration, avoid film cracking and grain boundary defects, and thus improve the crystallization quality of the perovskite film. By reducing the crystal defects caused by stress, the surface of the film becomes smoother and denser, significantly improving the stability of the film.
[0026] 2. Improve photoelectric conversion efficiency and device stability: The present invention not only improves the crystal structure of the perovskite film and reduces the defect state density by introducing small ions, but also enhances the interface contact performance between the film and the electron transport layer. These improvements have significantly improved the photoelectric conversion efficiency of perovskite solar cells. In addition, the long-term stability of the device has also been significantly improved, and it can maintain excellent performance in extreme environments such as light, heat, and humidity, making it suitable for long-term use.
[0027] 3. The process is simple and easy, suitable for large-scale production: The method of adding small ions proposed in the present invention is simple in process, easy to operate, and suitable for large-scale preparation. Compared with other complex stress control methods, the method of using small ions to regulate stress is low in cost and has strong applicability. This method is not only suitable for perovskite solar cells, but also can be used for the preparation of other types of perovskite optoelectronic devices, and has broad application prospects.
[0028] 4. Excellent device performance and commercial potential: The perovskite solar cells prepared by this method have a more compact film structure and excellent photoelectric performance, showing excellent photoelectric conversion efficiency and long-term stability. This method can not only improve the device performance in the laboratory environment, but also provide a reliable technical foundation for the commercial application of perovskite solar cells, which has great market potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:
[0030] Figure 1 This is a structural diagram of a perovskite solar device prepared in a nitrogen atmosphere according to the present invention;
[0031] FIG2 (a) and (b) are SEM images of a perovskite film with low defect state density and smooth and dense surface prepared in a nitrogen atmosphere according to the present invention and a perovskite film prepared without adding a small ion radius material;
[0032] 3(a) and (b) are grazing incidence wide-angle X-ray scattering images of the perovskite film prepared in a nitrogen atmosphere according to the present invention and the perovskite film prepared without adding a small ion radius material;
[0033] 4(a) and (b) are grazing incidence X-ray diffraction patterns of the perovskite film prepared in a nitrogen atmosphere and the perovskite film prepared without adding a small ion radius material according to the present invention;
[0034] Figure 5 It is a JV curve diagram of the perovskite solar cell prepared in a nitrogen atmosphere and the perovskite solar cell prepared without adding a small ion radius material;
[0035] Figure 6 It is a curve of the change of the photoelectric conversion efficiency of the perovskite solar cell prepared in a nitrogen atmosphere under illumination with time and the perovskite solar cell prepared without adding small ion radius materials in a nitrogen atmosphere under illumination. DETAILED DESCRIPTION
[0036] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0037] The method for eliminating internal stress in a perovskite film and a method for producing a perovskite solar cell provided by an embodiment of the present invention comprises the following steps:
[0038] Step 1: The FTO glass substrate is cleaned with detergent, deionized water, acetone and anhydrous ethanol in sequence, and each cleaning time is 20 minutes. Then, the FTO glass is dried and treated with UV-Ozone for 20 minutes.
[0039] Step 2, dissolving lead iodide, formamidine hydroiodide, methylamine hydrochloride and methylamine lead tribromide single crystal in a N, N-dimethylformamide / dimethyl sulfoxide mixed solvent (volume ratio of (5-10): (1-10)) according to a molar ratio of (1.5-1.6): (1.2-1.4): (0.3-0.5): (0.01-0.2), stirring for more than 3 to 6 hours, and fully mixing to obtain a perovskite precursor solution.
[0040] Step 3, dissolving tert-butylpyridine, tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris[bis(trifluoromethane)sulfonylimide] solution (50-100 mg of tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris[bis(trifluoromethane)sulfonylimide] in 100-1000 μL of acetonitrile), lithium bis(trifluoromethanesulfonylimide) solution, and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in an organic solvent of chlorobenzene, anisole or ethyl acetate in a mass ratio of (10-30):(1-10):(5-20):(10-100) to obtain a hole transport layer precursor solution.
[0041] Step 4: Prepare SnO on the cleaned FTO glass substrate by chemical bath deposition (CBD) method. 2 Electron transport layer.
[0042] Step 5, the FTO transparent conductive glass deposited with the electron transport material is treated with ultraviolet ozone for 10 minutes, then germanium iodide is added to the perovskite precursor solution, the perovskite precursor solution is injected into the nitrogen glove box, and the spin coating method is used to rotate at 1000-2000 rpm for 10-20 seconds, and then rotated at 5000-7000 rpm for 20-40 seconds; and 500 μL of anhydrous ether is added as an antisolvent in the last 15 seconds. After deposition, the perovskite film is placed in the glove box for aging for a while, and then annealed at 100-150°C for 0.5-3 hours.
[0043] After cooling to room temperature, n-octyl hydroiodide or 4-methoxyphenethylammonium iodide solution (dissolved in isopropanol, concentration of 3.5-4 mg / mL) was spin-coated at 3000-5000 rpm for 30-60 seconds, and immediately annealed at 100-150° C. for 5-8 minutes.
[0044] Figure 1 It is a structural diagram of a perovskite solar cell device prepared in a nitrogen atmosphere of the present invention. Figure 2 (a) and (b) are SEM images of a perovskite film with low defect state density, smooth and dense surface prepared in a nitrogen atmosphere of the present invention and a perovskite film prepared without adding a small ion radius material; Figure 3 (a) and (b) are grazing incidence wide-angle X-ray scattering images of a perovskite film prepared in a nitrogen atmosphere of the present invention and a perovskite film prepared without adding a small ion radius material.
[0045] Step 6: Spin-coat the FTO transparent conductive glass deposited with the perovskite layer at 4000-6000 rpm for 20-60 seconds to coat the hole transport layer on top of the perovskite layer.
[0046] Step 7, thermally evaporate a 100-200 nm thick gold electrode on the FTO transparent conductive glass deposited with a hole transport layer by thermal evaporation, and then oxidize the prepared device for more than 24 hours. A sufficient oxidation process helps to improve the device performance and obtain a perovskite solar cell.
[0047] Figure 4 (a) and (b) are grazing incidence X-ray diffraction patterns of the perovskite film prepared in a nitrogen atmosphere according to the present invention and the perovskite film prepared without adding small ion radius materials. It can be seen from the figures that adding small ion radius materials can significantly improve the quality and performance of the perovskite film. Figure 5 It is a JV curve diagram of the perovskite solar cell prepared in a nitrogen atmosphere and the perovskite solar cell prepared without adding a small ion radius material; Figure 6 The graph is a curve of the photoelectric conversion efficiency of the perovskite solar cell prepared in a nitrogen atmosphere and the perovskite solar cell prepared without adding a small ion radius material under illumination in a nitrogen atmosphere over time. It can be seen from the graph that adding a small ion radius material can significantly improve the quality and performance of the perovskite film.
[0048] The present invention is further described below through different embodiments.
[0049] Example 1
[0050] This embodiment is an inverted planar heterojunction solar cell prepared by a method for eliminating internal stress in a perovskite film and a method for preparing a perovskite solar cell, so as to fully understand the present invention, and mainly includes the following steps:
[0051] Step 1) The FTO glass substrate is cleaned with detergent, deionized water, acetone and anhydrous ethanol in sequence, with each cleaning time being 20 minutes. Then, the FTO glass is dried and treated with UV-Ozone for 20 minutes.
[0052] Step 2) Lead iodide, formamidine hydroiodide, methylamine hydrochloride and methylamine lead tribromide single crystals were dissolved in a N, N-dimethylformamide / dimethyl sulfoxide mixed solvent (volume ratio of 8:1) according to a molar ratio of 1.5:1.3:0.4:0.1, and stirred for more than 3 hours. Subsequently, germanium iodide was added to the perovskite precursor solution 8 minutes before spin coating, and fully mixed as a perovskite precursor solution for standby use.
[0053] Step 3) Dissolve 4-tert-butylpyridine, tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris(trifluoromethanesulfonylimide) solution (75 mg of tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris(trifluoromethanesulfonylimide) in 200 μL of acetonitrile), lithium bis(trifluoromethanesulfonylimide) solution (260 mg of lithium bis(trifluoromethanesulfonylimide) in 500 μL of acetonitrile) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in chlorobenzene in a mass ratio of 20:5:20:10, stir well and set aside as a hole transport layer precursor solution.
[0054] Step 4) Prepare SnO on the cleaned FTO glass substrate by chemical bath deposition (CBD) method 2 Electron transport layer.
[0055] Step 5) The FTO transparent conductive glass deposited with the electron transport material was treated with UV ozone for 10 minutes. Subsequently, germanium iodide was added to the perovskite precursor solution, and the perovskite precursor solution was spun at 1500 rpm for 15 seconds in a nitrogen glove box by spin coating, then spun at 6000 rpm for 30 seconds, and 500 μL of anhydrous ether was added as an antisolvent in the last 15 seconds. After deposition, the perovskite film was placed in a glove box for aging for a while, and then annealed at 100°C for 3 hours.
[0056] After cooling to room temperature, n-octyl hydroiodide or 4-methoxyphenethylammonium iodide solution (dissolved in isopropanol at a concentration of 3.5-4 mg / mL) was spin-coated at 4000 rpm for 50 seconds and immediately annealed at 100°C for 8 minutes.
[0057] Step 6) Spin-coating the FTO transparent conductive glass with the perovskite layer at 4000 rpm for 30 seconds to coat the hole transport layer on top of the perovskite layer.
[0058] Step 7) A 100 nm thick gold electrode is thermally evaporated on the FTO transparent conductive glass deposited with the hole transport layer by thermal evaporation, and then the prepared device is subjected to oxidation treatment for more than 24 hours. A sufficient oxidation process helps to improve the device performance.
[0059] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this example is 25.35%, the open circuit voltage is 1.182V, and the short circuit current is 25.23mA / cm 2 , the filling factor is 84.67%.
[0060] Example 2
[0061] Step 1) The FTO glass substrate is cleaned with detergent, deionized water, acetone and anhydrous ethanol in sequence, with each cleaning time being 20 minutes. Then, the FTO glass is dried and treated with UV-Ozone for 20 minutes.
[0062] Step 2) Lead iodide, formamidine hydroiodide, methylamine hydrochloride and methylamine lead tribromide single crystals were dissolved in a N, N-dimethylformamide / dimethyl sulfoxide mixed solvent (volume ratio of 8:1) according to a molar ratio of 1.6:1.2:0.3:0.2, and stirred for more than 3 hours. Subsequently, germanium iodide was added to the perovskite precursor solution 10 minutes before spin coating, and fully mixed as a perovskite precursor solution for standby use.
[0063] Step 3) Dissolve 4-tert-butylpyridine, tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris(trifluoromethanesulfonylimide) solution (75 mg of tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris(trifluoromethanesulfonylimide) in 200 μL of acetonitrile), lithium bis(trifluoromethanesulfonylimide) solution (260 mg of lithium bis(trifluoromethanesulfonylimide) in 500 μL of acetonitrile) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in chlorobenzene in a mass ratio of 30:1:5:100, stir well and set aside as a hole transport layer precursor solution.
[0064] Step 4) Prepare SnO on the cleaned FTO glass substrate by chemical bath deposition (CBD) method 2 Electron transport layer.
[0065] Step 5) The FTO transparent conductive glass deposited with the electron transport material was treated with UV ozone for 10 minutes. Subsequently, germanium iodide was added to the perovskite precursor solution, and the perovskite precursor solution was spun at 1000 rpm for 20 seconds in a nitrogen glove box by spin coating, then spun at 5000 rpm for 40 seconds, and 500 μL of anhydrous ether was added as an antisolvent in the last 15 seconds. After deposition, the perovskite film was placed in a glove box for aging for a while, and then annealed at 150°C for 0.5 hours.
[0066] After cooling to room temperature, n-octyl hydroiodide or 4-methoxyphenethylammonium iodide solution (dissolved in isopropanol at a concentration of 3.5-4 mg / mL) was spin-coated at 3000 rpm for 60 seconds and immediately annealed at 120°C for 6 minutes.
[0067] Step 6) Spin-coating the FTO transparent conductive glass with the perovskite layer at 6000 rpm for 20 seconds to coat the hole transport layer on top of the perovskite layer.
[0068] Step 7) A 150 nm thick gold electrode is thermally evaporated on the FTO transparent conductive glass deposited with the hole transport layer by thermal evaporation, and then the prepared device is subjected to an oxidation treatment for more than 24 hours. A sufficient oxidation process helps to improve the device performance.
[0069] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this example is 24.56%, the open circuit voltage is 1.166V, and the short circuit current is 25.12mA / cm 2 , the filling factor is 82.65%.
[0070] Example 3
[0071] Step 1) The FTO glass substrate is cleaned with detergent, deionized water, acetone and anhydrous ethanol in sequence, with each cleaning time being 20 minutes. Then, the FTO glass is dried and treated with UV-Ozone for 20 minutes.
[0072] Step 2) Lead iodide, formamidine hydroiodide, methylamine hydrochloride and methylamine lead tribromide single crystals were dissolved in a N,N-dimethylformamide / dimethyl sulfoxide mixed solvent (volume ratio of 8:1) according to a molar ratio of 1.55:1.4:0.5:0.01, and stirred for more than 3 hours. Subsequently, germanium iodide was added to the perovskite precursor solution 5 minutes before spin coating, and fully mixed as a perovskite precursor solution for use.
[0073] Step 3) Dissolve 4-tert-butylpyridine, tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris(trifluoromethanesulfonylimide) solution (75 mg of tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris(trifluoromethanesulfonylimide) in 200 μL of acetonitrile), lithium bis(trifluoromethanesulfonylimide) solution (260 mg of lithium bis(trifluoromethanesulfonylimide) in 500 μL of acetonitrile) and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in chlorobenzene in a mass ratio of 10:10:12:50, stir well and set aside as a hole transport layer precursor solution.
[0074] Step 4) Prepare SnO on the cleaned FTO glass substrate by chemical bath deposition (CBD) method 2 Electron transport layer.
[0075] Step 5) The FTO transparent conductive glass deposited with the electron transport material was treated with UV ozone for 10 minutes. Subsequently, germanium iodide was added to the perovskite precursor solution, and the perovskite precursor solution was spun at 2000 rpm for 10 seconds in a nitrogen glove box by spin coating, then spun at 7000 rpm for 20 seconds, and 500 μL of anhydrous ether was added as an antisolvent in the last 15 seconds. After deposition, the perovskite film was placed in a glove box for aging for a while, and then annealed at 120°C for 2 hours.
[0076] After cooling to room temperature, n-octyl hydroiodide or 4-methoxyphenethylammonium iodide solution (dissolved in isopropanol at a concentration of 3.5-4 mg / mL) was spin-coated at 5000 rpm for 30 seconds and immediately annealed at 150°C for 5 minutes.
[0077] Step 6) Spin coating the FTO transparent conductive glass deposited with the perovskite layer at 5000 rpm for 60 seconds to coat the hole transport layer on top of the perovskite layer.
[0078] Step 7) A 200 nm thick gold electrode is thermally evaporated on the FTO transparent conductive glass deposited with the hole transport layer by thermal evaporation, and then the prepared device is subjected to oxidation treatment for more than 24 hours. A sufficient oxidation process helps to improve the device performance.
[0079] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this example is 23.88%, the open circuit voltage is 1.180V, and the short circuit current is 25.09mA / cm 2 , the filling factor is 81.17%.
[0080] It can be seen from the above examples that the photoelectric conversion efficiency of the perovskite solar cell prepared by the present invention is not less than 23.88%, the open circuit voltage is 1.182V, and the short circuit current is not higher than 25.23mA / cm 2 , the filling factor is not less than 81.17%. It has excellent electron extraction and transmission capabilities, a flat and dense surface, and good water and oxygen barrier capabilities, which greatly improves the photoelectric conversion efficiency and device stability of perovskite solar cells.
[0081] The present invention is based on the fact that during the deposition and annealing process of the traditional perovskite film, stress concentration often leads to film cracking, increased grain boundary defects, and decreased film quality, which ultimately affects the performance and stability of the perovskite solar cell. The present invention introduces specific small ions into the perovskite precursor solution, which can effectively combine with the perovskite lattice or be distributed at the grain boundary, adjust the stress distribution of the film, reduce the stress concentration phenomenon, thereby relieving the stress in the film, regulating the crystal growth process, not only improving the crystallization quality of the film, but also significantly reducing the defect state density in the film, thereby improving the photoelectric conversion efficiency and long-term stability of the device, thereby preparing an efficient and stable perovskite solar cell.
[0082] The perovskite solar cells prepared by this method have a denser and smoother film surface and excellent interface contact performance because their film stress is effectively released, which enables the device to exhibit excellent photoelectric conversion efficiency and long-term stability, and has great commercial application prospects.
[0083] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A method for preparing a perovskite solar cell for eliminating stress of a perovskite film, characterized in that: The following steps are involved: (1) Clean the FTO glass substrate, dry it, and then treat it with ultraviolet ozone; (2) dissolving lead iodide, formamidine hydroiodide, methylamine hydrochloride and methylamine lead tribromide single crystal in a mixed solvent in a molar ratio of (1.5-1.6):(1.2-1.4):(0.3-0.5):(0.01-0.2) to obtain a perovskite precursor solution; (3) dissolving tert-butylpyridine, tert-butylpyridine-sulfonyl imide solution, lithium bis(trifluoromethanesulfonyl imide) solution and 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene in an organic solvent in a mass ratio of (10-30):(1-10):(5-20):(10-100) to obtain a hole transport layer precursor solution; (4) Preparing a SnO2 electron transport layer on the cleaned FTO glass substrate by a chemical bath deposition method; (5) adding germanium iodide to a perovskite precursor solution on a FTO transparent conductive glass on which an electron transport material is deposited, and spin coating the perovskite precursor solution by a spin coating method; Then, the anti-solvent method is used for spin coating, and the perovskite layer is obtained after annealing; (6) spin coating a hole transport layer precursor solution on the FTO transparent conductive glass deposited with the perovskite layer to obtain a hole transport layer coated on the perovskite layer; (7) A metal electrode is thermally evaporated on the FTO transparent conductive glass deposited with a hole transport layer to obtain a perovskite solar cell.
2. The method for preparing a perovskite solar cell for eliminating perovskite film stress according to claim 1, characterized in that: The mixed solvent is prepared by mixing N,N-dimethylformamide / dimethyl sulfoxide in a volume ratio of (5-10): (1-10).
3. The method for preparing a perovskite solar cell for eliminating perovskite film stress according to claim 1, characterized in that: The tert-butylpyridine-sulfonyl imide solution is prepared by dissolving 50-100 mg of tris(2-(1H-pyrazol-1-yl)-4-tert-butylpyridine)cobalt(III)tris[bis(trifluoromethane)sulfonyl imide] in 100-1000 μL of acetonitrile.
4. The method for preparing a perovskite solar cell for eliminating perovskite film stress according to claim 1, characterized in that: The organic solvent is one or more of chlorobenzene, anisole or ethyl acetate.
5. The method for preparing a perovskite solar cell for eliminating perovskite film stress according to claim 1, characterized in that: In the step (5), the perovskite precursor solution is spin-coated by a spin coating method, including: using ultraviolet ozone to treat FTO transparent conductive glass deposited with electron transport material, and the perovskite precursor solution is placed in a nitrogen atmosphere and spin-coated at a low speed of 1000-2000 rpm for 10-20 seconds, and then at a high speed of 5000-7000 rpm for 20-40 seconds.
6. The method for preparing a perovskite solar cell for eliminating perovskite film stress according to claim 5, characterized in that: In the step (5), the anti-solvent method is used for spin coating and annealing, comprising: In the last 15 seconds of high-speed rotation, anti-solvent anhydrous ether is added for deposition, and the perovskite film is aged and annealed at 100-150°C for 0.5-3 hours; cooled to room temperature, iodate solution is spin-coated at a rotation speed of 3000-5000 rpm for 30-60 seconds, and immediately annealed at 100-150°C for 5-8 minutes.
7. The method for preparing a perovskite solar cell for eliminating perovskite film stress according to claim 6, characterized in that: The iodate solution is n-octylamine hydroiodide or 4-methoxyphenethylammonium iodide dissolved in isopropanol, with a concentration of 3.5-4 mg / mL.
8. The method for preparing a perovskite solar cell for eliminating perovskite film stress according to claim 1, characterized in that: In the step (6), the hole transport layer precursor solution is spin-coated on the FTO transparent conductive glass deposited with the perovskite layer at 4000-6000 rpm for 20-60 seconds; In the step (7), the metal electrode thermally evaporated on the FTO transparent conductive glass deposited with the hole transport layer is a gold electrode with a thickness of 100 to 200 nm.
9. A perovskite solar cell prepared by the method according to any one of claims 1 to 8 and eliminating the stress of the perovskite film.
10. Application of the perovskite solar cell for eliminating perovskite film stress according to claim 9 in the field of optoelectronics.
Citation Information
Patent Citations
High-efficiency low-cost copper indium gallium selenium / perovskite double-junction solar photocell prepared through all-solution method
CN104022225A
Preparation method of organic-inorganic perovskite solar cell
CN116419643A
Method for preparing efficient and stable perovskite solar cell through low-temperature process
CN116867334A
Perovskite solar cell and preparation method therefor
EP4304317A1
Organic-inorganic perovskite solar cell with directional arrangement of intrinsic perovskite dipoles and preparation method thereof
US20240114759A1